THE BRITISH NEIGHBOURHOOD POLICING MODEL: ADAPTATION POTENTIAL IN UZBEKISTAN (TSUL LEGAL REPORT, 2026)
This article examines the institutional, legal, and practical aspects of the British neighbourhood policing model, as implemented in London, to assess its adaptability to Uzbekistan. Employing a methodological blend of comparative legal analysis, institutional theory, and empirical sociological methods, the study evaluates the model’s core elements, drawing on UK legislation (e.g., National Security Act 2023), the City of London Police Strategy (2024–2025), and Office for National Statistics data. Key features include administrative clustering, Dedicated Ward Officers, Partnership and Prevention Hubs, Cluster Panel Meetings, and the Community Profile digital tool, underpinned by evidence-based policing, territorial accountability, transparency, and participatory governance. A sociological survey in Uzbekistan (n=300) highlights strong spatial identity, public willingness to collaborate with law enforcement, and demand for enhanced police visibility. The article proposes adapting the model through Uzbekistan’s National Guard, introducing a Mahalla Community Profile, analytical hubs, and cluster-based community engagement. An adaptation algorithm is outlined, focusing on regulatory frameworks, personnel professionalization (aligned with ProQual Level 3), digital security management, and feedback mechanisms. The study’s novelty lies in its strategic approach to localizing a foreign policing model, accounting for Uzbekistan’s cultural, spatial, and institutional contexts. Its findings offer theoretical insights for policing reform and practical guidance for public safety policies in developing nations.